Multi-objective optimization in learn to pre-compute evidence fusion to obtain high quality compressed web search indexes - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The world of information retrieval revolves around web search engines. Text search engines are one of the most important source for routing information. The web search engines index huge volumes of data and handles billions of documents. The learn to rank methods have been adopted in the recent past to generate high quality answers for the search engines. The ultimate goal of these systems are to provide high quality results and, at the same time, reduce the computational time for query processing. Drawing direct correlation from the aforementioned fact; reading from smaller or compact indexes always accelerate data read or in other words, reduce computational time during query processing. In this thesis we study about using learning to rank method to not only produce high quality ranking of search results, but also to optimize another important aspect of search systems, the compression achieved in their indexes. We show that it is possible to achieve impressive gains in search engine index compression with virtually no loss in the final quality of results by using simple, yet effective, multi objective optimization techniques in the learning process. We also used basic pruning techniques to find out the impact of pruning in the compression of indexes. In our best approach, we were able to achieve more than 40% compression of the existing index, while keeping the quality of results at par with methods that disregard compression.
Keywords: Otimização Multi-Objetivo; Combinação Linear Convexo; Geométrico Médio Ponderado; Algoritmo Evolutivo Pareto; Compressão do Índice; Multi-Objective Optimization; Linear Convex Combination; Weighted Geometric Mean; Pareto Evolutionary Algorithm; Index Compression; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO